Mesoscale processes in the polar atmosphere : radar remote sensing, balloon-borne in situ measurements and modelling - Mihalikova, Maria (Luleå tekniska universitet, Rymdteknik, 2013)
Mesoscale processes (atmospheric phenomena with horizontal scales ranging from a few tens to several hundred kilometres and lasting from a few tens of minutes to a few days) have the potential to influence the chemical composition of the troposphere. Tropopause folds and mountain waves are two important types of mesoscale processes. Concentrations and gradients of trace gases like ozone (O3) can be influenced by these processes. Tropopause folds bring ozone-rich stratospheric air to lower altitudes. Mountain waves and turbulence associated with them influence O3 gradients in the troposphere. Tropospheric O3 is a toxic pollutant and a short-lived greenhouse gas with an influence on the lifetime of many other trace gases. Understanding of its long-term development and budgets are important. For this, better understanding, generalization and representation of mesoscale processes are necessary. Observations made by the 52MHz wind-profiler radar ESRAD (ESrange RADar) and the 54.5MHz wind-profiler radar MARA (Movable Atmospheric Radar for Antarctica) served as the basis for this study. ESRAD is located close to Kiruna in arctic Sweden and has been in operation since July 1996. This is a site with frequent mountain wave activity. By analysis of ESRAD and sonde data we have studied vertical mixing and turbulence associated with mountain waves. An attempt was made to show the influence of these processes on relaxation of the O3 gradient in the lower troposphere. Additional balloon-borne in situ measurements of vertical profiles of atmospheric characteristics (temperature, humidity, O3 mixing ratio) complement the radar measurements and aid in correct identification and improved understanding of the observed processes as well as of the radar backscatter signal itself. MARA was operated at the Swedish summer station Wasa (73°S, 13.5°W) during austral summer 2010/2011 and at the Norwegian year-round station Troll (72°S, 2.5°E) nonstop since December 2011. During its operation at the Wasa station, ozonesonde measurements ...